Penjatuhan Pidana Bersyarat Dan Pengawasannya Sebagai Alternatif Pemidanaan - Zikrul Hakim; Alvi Syahrin; Muhammad Hamdan; Mahmud Mulyadi (Universitas Sumatera Utara, 2019)
Abstract. The UUD 1945 defines that the Republic of Indonesia is a law state in which the efforts to halt the violence are regulated in KUHP. Article 10 of KUHP describes the types of criminal acts in Indonesia. Not only does the law cluster the type of the actions and their punishment, but also there is a system of imposing of other punishment such as probation which is not a sort of criminal acts described in the KUHP but is an alternative sanction in trial proceedings. Probation is still barely imposed by the judges and its implementation is still lack of supervision from the government. This research explains how important is to impose a probation as an alternative sanction, what is the procedure of supervision in probational decision, and what is the policy of criminal law in KUHP bill regarding of probation. The method used in this research is descriptive norm analysis. The research is also supported by the interview of the officials to provide enough data about the result of the research. The result of the research shows that probation is one of very important alternatives for the convicts to improve their behaviour, to avoid sub-culture of imprisonment and over-crowded in rehabilitation centre. The procedure of supervising the behaviour of a person who is put on probation after that person released from the jail is yet to be regulated by the government. This has caused the chaos and uncertainty among the probation officials. They face many obstacles in implementation of the post-probation control. As the result, post-probationcontrolling process is not effectively implemented. The formulation of the parole in KUHP bill should focus on the types of crimes and length of punishment and supervision process, special and general condition for a person who is under official supervision, and the guidelines of implementation of under-surveillance punishment. Keywords : probation, supervision, alternatives punishment.